2017
DOI: 10.1002/gps.4724
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of neuroimaging in delirium: predictors, correlates and consequences

Abstract: Neuroimaging is now used more widely in delirium research due to advances in technology. However, imaging delirious patients presents challenges leading to methodological limitations and restricted generalisability. The findings that atrophy and WMH burden predict delirium replicates findings from the original review, while advanced techniques have identified other substrates and mechanisms that warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 69 publications
8
57
0
1
Order By: Relevance
“…Some studies reported generalized or focal (temporal lobe, limbic system) grey matter atrophy to increase the risk for delirium while others did not find this association (69,110). A recent review interpreted differences in structural imaging to be mainly due to the focus on cardiac surgery and ICU patients that are difficult to generalize (67). Our study provides several potential benefits regarding mentioned limitations.…”
Section: Structural and Functional Imagingmentioning
confidence: 69%
See 1 more Smart Citation
“…Some studies reported generalized or focal (temporal lobe, limbic system) grey matter atrophy to increase the risk for delirium while others did not find this association (69,110). A recent review interpreted differences in structural imaging to be mainly due to the focus on cardiac surgery and ICU patients that are difficult to generalize (67). Our study provides several potential benefits regarding mentioned limitations.…”
Section: Structural and Functional Imagingmentioning
confidence: 69%
“…(11,68). A recent review found that most research in the field was done in cardiovascular surgery or ICU patients limiting the generalizability of previous findings (67). Moreover, only two patient cohorts were prospectively evaluated for MRI changes following an episode of delirium and none of the studies had a focus on POD or POCD (11,69,70).…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…Neuroimaging is a further method that has been increasingly used to understand the neural correlates of delirium. The systematic review on this topic by Nitchingham and colleagues finds that there is increasing evidence of structural and functional abnormalities associated with delirium. Further work is required to understand better how best to deploy neuroimaging in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Demnach werden prodopaminerge und anticholinerge Substanzen als delirogen angesehen [8]. Beim Delir zeigen sich außerdem eine Desorganisation neuronaler Netzwerke, erfasst mittels funktioneller und struktureller Konnektivitätsanalysen [9], ein globaler und regionaler zerebraler Hypometabolismus und Veränderungen der zerebralen Perfusion [10], die ebenfalls als Bestandteile der gemeinsamen neurobiologischen Endstrecke des Delirs angesehen werden. An der Aktivierung der gemeinsamen Endstrecke dürften eine gestörte Stressantwort und immunologische Prozesse beteiligt sein.…”
unclassified